A place called Brunei - Ashton, Chris ([S.l.] : Peter Pan Production [production company] ; Hong Kong : Educational Film Services [distributor], 1984)
Describe on the history of Brunei, social life and customs, politics and government and also the rulers of Brunei, Sultan Hasanal Bolkiah.
Copy available in DVD format
Writer, Chris Ashton ; director, Chris Ashton
Narrator: Hugh Keays-Byrne
Keywords: Brunei -- History; Brunei -- Politics and government -- History; Brunei -- Economic conditions